Essential Oil Composition of Endemic Centaurea tchihatcheffii Fisch. and Mey. from Turkey - ALTINTAS, AYHAN; KOCA, UFUK; DEMIRCI, BETUL; HUSNU CAN BASER, K. (Asian Journal of Chemistry, 2010)
The essential oil obtained by hydrodistillation from endemic Centaurea tchihatcheffii Fisch. & Mey. (Asteraceae) from Turkey was analyzed by gas chromatography (GC) and gas chromatography/mass spectrometry (GC/MS), simultaneously. Main constituents of the oil were found as caryophyllene oxide (15.1 %), carvacrol (14.7 %), acetophenone (6.2 %) and spathulenol (5.3 %).